Artificial Intelligence (AI) in Psychiatry – A Summary (Global Journal of Medical Research, 2022)
This bibliographic review appraises Artificial Intelligence AI theory s applications for psychiatry Globally hundreds of millions of people suffer from mental diseases Hundreds of thousands of people in the world commit suicide and also die from illicit drug overdose due to addiction Diagnosis and therapy of psychiatric diseases are complex and machine computer diagnostic tools for physicians are urgently needed to bolster their decision making This study includes various applications AI machine learning algorithms in various sub-specialties of psychiatry AI ML based psychiatry offers better value over conventional psychiatry in mood disorders learning disability children and adolescents mental illnesses substance abuse However numerous implementation challenges for AI in clinical psychiatric practice still remain